Music Technology: A Synaesthesia for Music Education in Contemporary Societies - Amaegbe, James Esinkuma (Acta Universitatis Danubius. Communicatio, 2023)
Music technology is becoming an integral part of music education in the 21 st century. It is revolutionizing the way music education is taught in contemporary society. Music technology is changing the way music students learn and do music, as such opening up new possibilities for creativity and expression of music. Thus, technology has made music education so global that students can learn from digital audio workstations (daw) to online communities for sharing music, and music ideas and patterns of applications. Technology is reshaping the field of music education. This research explores the impact of music technology on music education, and how it can enhance and enriches the learning processes; including the ways it promotes creativity, collaboration, and engagements. It also examines the challenges associated with integrating music technology in the classroom, and the opportunities it posits for the future of music education. The findings of the study suggest that music technology can be a powerful and strategic tool for promoting creativity, collaboration, and engagements in music education, and can also assist in creating a more immersive and holistic teaching and learning experience.